Integration of SWOT Analysis and Analytical Hierarchy Process (AHP) in Determining the Location of Pamelo Orange Processing Industry in Pangkep Regency - Andi Ridwan Makkulawu; Ilham Ahmad; Andryanto Aman; Imran Muhtar; Ismail Gaffar; Nurhana Febrianti (Jurnal Penelitian Pendidikan IPA, 2023)
Until now, many analyzes have been carried out to determine the right industrial location. However, there has been no attempt to combine SWOT analysis and the Analytical Hierarchy Process (AHP) in this context. This study aims to determine a strategic location as a place to establish a pomelo orange processing industry in Pangkep Regency by integrating SWOT and AHP analysis. The factors in the SWOT analysis were obtained through interviews with various related parties, followed by the distribution of the SWOT and AHP questionnaire surveys to 5 respondents who were considered experts in their fields, consisting of 3 management lecturers from the Pangkep State Agricultural Polytechnic and 2 parties from the Department of Agriculture and the Department of Agriculture. Pangkep Regency Industry. The results of the SWOT and AHP analysis reveal 6 factors that have high priority in determining the location of the pomelo orange processing industry in Pangkep Regency, namely raw material availability, land availability, distance from the city center, taxation aspects, support from the local government, and legality factors. Based on the conclusions of these six priority factors, it can be suggested that the most strategic location for the pomelo orange processing industry in Pangkep Regency is in Ma'rang District